AXA : creating new CR metrics - Elias, Jaan; Rosenthal, Jean W., 1945-; Cort, Todd; Bach, David ([London] : SAGE, 2016)
A global leader in the insurance and asset management business, AXA had risen to the top ranks in terms of corporate responsibility (CR) as well. Not content to rest on these laurels, AXA reorganized its CR team into a department with strategy, inspiring a reconsideration of how AXA monitored and measured its CR efforts. The CR group was now looking to create new metrics that tied CR work more closely to AXA's operations and growth.
Originally Published in: Elias, J., Rosenthal, J., Cort, T., & Bach, D. (2015). AXA: Creating New CR Metrics. 101-15. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://nexus.som.yale.edu/axa.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; AXA Insurance (Firm); Social responsibility of business -- Case studies; Sustainable development -- Case studies; Strategic planning -- Case studies